MODULATING IMPACT OF ELECTROMAGNETIC RADIATION ON GEOACOUSTIC EMISSION OF ROCKS - Gavrilov V.A.; Panteleev I.A.; Ryabinin G.V.; Morozova Y.V. (My University, 2013)
This work presents the results of studies of a physical basis of modulating effects of continuous exposure to electromagnetic radiation on intensity of geoacoustic processes in real geological media. The study is based on data from long-term borehole geoacoustic, electromagnetic, hydrogeochemical and hydrogeodynamic measurements performed in the Petropavlovsk-Kamchatsky geodynamic polygon. The authors have analyzed the physical reasons for the high correlation of the RMS signals of geoacoustic emission and external electromagnetic radiation at intervals of background seismicity and investigated the physical mechanism of the effect of degradation of geoacoustic emission response to the electromagnetic effects observed at the time of relatively close strong earthquakes.
Keywords: GEOACOUSTIC EMISSION; ELECTROMAGNETIC RADIATION; BOREHOLE; MODULATING IMPACT; HYDROCHEMICAL RESEARCH; STRONG EARTHQUAKES; KAMCHATKA REGION; MONITORING; DILATANCY; COMPRESSIVE STRESS